Application of microporous and mesoporous metal organic framework microsphere material in organic dye and heavy metal wastewater
By forming UiO-66-NH2 and ZIF-67 microsphere nanomaterials with both microporous and mesoporous on block copolymer microspheres, the problem of insufficient removal efficiency of organic dyes and heavy metal ions contaminated water in the prior art is solved, and efficient and stable adsorption effect is achieved.
Patent Information
- Application Number
- CN202411726407.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The prior art is difficult to efficiently remove organic dyes and heavy metal ions contaminated water, especially methylene blue and chromium (VI) contaminants, and traditional adsorbents have insufficient stability and efficiency.
UiO-66-NH2 and ZIF-67 microsphere nanomaterials with both microporous and mesoporous are self-assembled on block copolymer microspheres, and efficient adsorption of methylene blue and Cr(VI) solutions is achieved using their high specific surface area and structural regulation.
The rapid and efficient adsorption of methylene blue and Cr (VI) solutions was achieved, with an adsorption capacity increased by 13.6-14.7%, and the material itself has good chemical and thermal stability.
Smart Images

Figure CN119565574A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to UiO-66-NH having both micropores and mesopores. 2 Preparation of ZIF-67 micron-sized microsphere nanomaterials and their application in adsorbing organic dyes and heavy metal wastewater Background Art
[0002] Organic dyes, heavy metal ions and other pollutants pollute water quality, causing serious environmental problems. Among them, methylene blue (MB) is toxic, carcinogenic and non-biodegradable. The harmful compounds (such as sulfur oxides, nitrogen oxides, carbon monoxide) produced by its decomposition are closely related to serious diseases such as cancer, gastritis, and hypertension. Chromium (Cr) is a common pollutant in surface water and groundwater, and is widely used in electroplating, leather making, printing, pigments, polishing and other industries. Aquatic systems and drinking water sources contaminated by Cr (VI) can increase the risk of severe diarrhea and bladder cancer, liver cancer, kidney cancer and skin cancer, posing a serious threat to the environment and human health. Even at lower concentrations, Cr (VI) can still cause harm to the human body due to its high toxicity, carcinogenicity and bioaccumulation through the food chain.
[0003] According to research, adsorption is the best technology for removing dyes and heavy metal wastewater. Compared with traditional adsorbents such as activated carbon and nanoparticles, MOFs have higher specific surface area and high porosity. At the same time, the structure of MOFs materials can be adjusted and modified according to the specific adsorption object to improve the adsorption force between the material and the target molecule. The present invention uses amphiphilic block copolymer (PS-b-PAA) microspheres self-assembled in a selective solvent. The microspheres have regular and highly dense mesoporous micron-sized particles. They are used as soft templates to produce UiO-66-NH with both micropores and mesopores formed by the mutual growth of metal-organic framework nanocrystals. 2 and ZIF-67 micron-sized microspheres, which were used for dye adsorption and heavy metal ion adsorption, respectively, and their adsorption performance and mechanism were investigated. Summary of the invention
[0004] The present invention provides a metal organic framework microsphere material with both micropores and mesopores and a synthesis method, which has a larger specific surface area and provides more active sites. The metal organic framework microsphere particle material has a high adsorption capacity for methylene blue aqueous solution and Cr (VI) solution, and also has good chemical stability and thermal stability.
[0005] The present invention adopts the following technical solution to solve the above technical problems, a method for synthesizing metal organic framework microspheres with both micropores and mesopores. The preparation route of the metal organic framework microspheres with both micropores and mesopores is as follows:
[0006] (1) The amphiphilic block copolymer polystyrene-block-polyacrylic acid is dissolved in a mixed solvent of toluene / methanol, stirred for a certain period of time under magnetic stirring, and then a large amount of methanol is added to fix the obtained mesoporous spheres, and the obtained mesoporous spheres are collected by centrifugation, and the mesoporous spheres are dispersed in an alcohol solution to be uniformly dispersed to obtain solution 1.
[0007] (2) Add 2-aminoterephthalic acid / 2-methylimidazole alcohol solution to the above solution 1, and stir the two solutions in an oil bath at 70°C / room temperature to obtain solution 2. Add zirconium tetrachloride / cobalt nitrate hexahydrate alcohol solution and catalyst formic acid to solution 2 and continue stirring. Cool to room temperature and record as solution 3. Wash the product several times with ultrapure water, ethanol, and DMF.
[0008] (3) After centrifuging solution 3, the obtained product is placed in DMF and stirred at room temperature. Finally, it is washed with DMF, ultrapure water, and ethanol to remove the polymer soft template and then dried in a vacuum oven for 12-24 hours. The obtained substance is the metal organic framework microsphere particles.
[0009] UiO-66-NH 2 It is a type of zirconium metal MOFs with extremely strong water stability. It can adsorb pollutants more efficiently. ZIF-67 has a hydrophobic surface, high chemical and thermal stability, simple synthesis operation, and can be synthesized at room temperature. Therefore, these two MOFs were selected to be loaded on polymer microspheres and subsequent adsorption experiments were carried out.
[0010] Preferably, 2 ml of 10 mg / ml 2-aminoterephthalic acid ethanol solution is added to 4 ml of PS-b-PAA microsphere alcohol solution and stirred for 60 minutes, followed by the addition of 2 ml of 20 mg / ml zirconium tetrachloride ethanol solution and 2 ml of 3M formic acid aqueous solution; the resulting mixture is placed in an oil bath at 70°C for 12 hours; then PS-b-PAA@UiO-66-NH 2 The reaction mixture was cooled to room temperature, and the precipitate was collected by centrifugation. The precipitate was washed several times with ethanol and ultrapure water to obtain PS-b-PAA@UiO-66-NH 2 The prepared composite material PS-b-PAA@UiO-66-NH 2 The microspheres were immersed in N,N'-dimethylformamide (DMF) to dissolve the block copolymer PS-b-PAA part, and the resulting product was collected by centrifugation and washed several times with DMF and methanol. Finally, it was dried under vacuum at 60 °C for 12 h to produce UiO-66-NH 2 Microspheres.
[0011] 2 ml of 40 mg / ml 2-methylimidazole methanol solution was added to 4 ml of PS-b-PAA microsphere methanol solution and stirred for 60 min. Then, 2 ml of Co(NO 3 ) 2 6H 2 O 35mg / ml methanol solution; then the resulting mixture was stirred at room temperature for 24 hours; the PS-b-PAA@ZIF-67 reaction mixture was cooled to room temperature, the precipitate was collected by centrifugation, and the precipitate was washed several times with methanol to obtain PS-b-PAA@ZIF-67 microspheres. The prepared composite material PS-b-PAA@ZIF-67 microspheres were immersed in N, N'-dimethylformamide (DMF) to dissolve the block copolymer PS-b-PAA part, the resulting product was collected by centrifugation, and then washed several times with DMF and methanol. Then dried at 60 ° C under vacuum conditions for 12h to produce ZIF-67 microspheres with both micropores and mesopores.
[0012] Preferably, 5 mg of amino metal organic framework UiO-66-NH 2 The microspheres were stirred at 20-50 ℃ for 5-60 min, and the adsorption capacity was the highest at 80 mg / L and 50 ℃, which could reach 696.59 mg / g. 5 mg of metal organic framework ZIF-67 microspheres were added to 5-40 mol / L Cr (VI) solution and stirred at 20-50 ℃ for 5-180 min. The adsorption capacity was the highest at 40 mg / L and 50 ℃, which could reach 148.11 mg / g.
[0013] Preferably, 5 mg of amino metal organic framework UiO-66-NH 2 When the microspheres were stirred at room temperature for 30 min, the maximum adsorption rate could reach 93.85%; when 5 mg of metal organic framework ZIF-67 microspheres were added to 5 mol / L Cr (VI) solution and stirred at room temperature for 90 min, the maximum adsorption rate could reach 90.18%.
[0014] Preferably, in step (2), UiO-66-NH 2 The solvent used for the microspheres is ethanol, and the catalyst is formic acid. Compared with DMF and ultrapure water, ethanol will not destroy the morphology of the microspheres. Formic acid is more acidic than acetic acid. Adding a small amount of formic acid can achieve a good catalytic effect.
[0015] Preferably, after adding zirconium tetrachloride alcohol solution in step (2), the stirring temperature should be 70°C for 12 hours. If the temperature is greater than 100°C, the microsphere template will be destroyed. If the temperature is too low or the reaction time is too short, the MOF cannot grow completely.
[0016] Preferably, after adding the cobalt nitrate hexahydrate alcohol solution in step (2), the mixture is stirred at room temperature for 24 hours, the molar ratio of the organic ligand 2-methylimidazole:metal cobalt nitrate hexahydrate is 4:1, and the concentrations of the organic ligand 2-methylimidazole and the metal cobalt nitrate hexahydrate methanol are 40 mg / L and 35 mg / L, respectively.
[0017] Preferably, the stirring time for removing the soft template using the polymer good solvent DMF in step (3) should be greater than 24 h. If the time is less than 24 h, the template cannot be completely removed.
[0018] UiO-66-NH has both micropores and mesopores. 2 The ZIF-67 microspheres were used to adsorb methylene blue aqueous solution and Cr(VI) solution. The specific adsorption test was as follows: 20 and 40 mol / L methylene blue aqueous solution and 5 and 10 mol / L Cr(VI) solution were prepared, and 5 mg UiO-66-NH 2 and ZIF-67 micron-sized microsphere particles, and stirred at room temperature for 5-180 min. The absorbance at the maximum absorption wavelength was observed using an ultraviolet spectrophotometer, and the adsorption capacity at 20-50 °C was calculated to study the adsorption rate at different temperatures and concentrations. A control group was set up to study the single UiO-66-NH 2 and the adsorption capacity of ZIF-67 nanoparticles under the same conditions.
[0019] Beneficial effects:
[0020] The present invention uses a simple hydrothermal method to complex the metal with the carboxyl groups on the polymer microspheres, and a thin layer of MOF seeds grows on the pore walls and surfaces of the block copolymer mesoporous microspheres to form a PS-b-PAA@MOF composite material. Finally, the soft template is dissolved with a polymer good solvent to obtain UiO-66-NH with both mesopores and micropores. 2 , ZIF-67 microspheres. The prepared microspheres are used for the adsorption of organic dye methylene blue and heavy metal hexavalent chromium solution. The MOF microspheres can be adsorbed quickly and efficiently in a short time, and the adsorption capacity is increased by 13.6-14.7% compared with simple MOF nanoparticles. At the same time, the material itself has excellent stability.
[0021] Comparative Example 1 shows that Figure 2 By observing the SEM images under different preparation conditions, it can be found that when ultrapure water is used as the solvent, the surface of the PS-b-PAA microspheres appears to be agglomerated spherical. When DMF is used as the solvent, DMF will dissolve the PS-b-PAA microspheres and the microspheres will rupture. When ethanol is used as the solvent, UIO-66-NH 2Nanoparticles grow well on the surface of microspheres. When the reaction temperature is 30℃ and the reaction time is 5h, it can be observed that the MOF particles grow incompletely. When the reaction temperature is 100℃, the temperature is too high to destroy the morphology of the polymer soft template and the microspheres are broken. Therefore, by screening the conditions, UIO-66-NH 2 The best conditions for the microspheres were to use ethanol as the reaction solvent and react in an oil bath at 70 °C for 12 h.
[0022] Comparative Example 2 shows that Figure 4 By observing the SEM images of PS-b-PAA@ZIF-67 microspheres under different reaction conditions, it can be found that with the increase of the molar ratio, the particle size of ZIF-67 decreases accordingly. When the molar ratio of organic ligand to metal is 4:1, ZIF-67 nanoparticles grow well on PS-b-PAA microspheres. When the concentrations of 2-methylimidazole and cobalt nitrate hexahydrate methanol solution are 20 mg / L and 17.5 mg / L, respectively, fewer ZIF-67 nanoparticles are formed on the surface of PS-b-PAA microspheres. When the reaction time is 5h and 12h, the ZIF-67 precursor solution does not react fully with the PS-b-PAA microspheres. Therefore, through screening conditions, the optimal conditions for synthesizing ZIF-67 microspheres are a molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate of 4:1, and the concentrations of 2-methylimidazole and cobalt nitrate hexahydrate methanol solution are 40 mg / L and 35 mg / L, respectively, and the reaction is carried out at room temperature for 24h. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the SEM image of PS-b-PAA microspheres;
[0024] Figure 2 PS-b-PAA@UiO-66-NH under different reaction conditions 2 SEM images of microspheres;
[0025] Figure 3 This is the SEM image of UiO-66-NH2 microspheres obtained after optimizing the experimental conditions;
[0026] Figure 4 SEM images of PS-b-PAA@ZIF-67 microspheres under different reaction conditions;
[0027] Figure 5 This is the SEM image of ZIF-67 microspheres obtained after optimizing the experimental conditions;
[0028] Figure 6 UiO-66-NH 2 BET plot of microspheres;
[0029] Figure 7 is the BET diagram of ZIF-67 microspheres;
[0030] Figure 8 UiO-66-NH 2 XRD patterns of microspheres immersed in different organic solvents
[0031] Fig. 9 XRD patterns of ZIF-67 microspheres immersed in different organic solvents
[0032] Fig.10 UiO-66-NH 2 Microspheres, UiO-66-NH 2 The adsorption effect of nanoparticles on methylene blue aqueous solution;
[0033] Fig.11 This is a diagram showing the adsorption effect of ZIF-67 microspheres and ZIF-67 nanoparticles on Cr (VI) solution. DETAILED DESCRIPTION
[0034] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0035] Example 1
[0036] Preparation of block copolymer microspheres
[0037] 10 mg of block copolymer polystyrene-block-polyacrylic acid (PS-b-PAA) was dissolved in a mixed solvent (1.5 ml) of toluene and methanol with a volume ratio of 1:3, stirred at 800 rpm for 10 h under magnetic stirring, and then five times the volume of methanol was added to quench the structure and fix the morphology of the obtained mesoporous spheres, and the solid was collected by centrifugation. The solid was then redispersed in 5 ml of methanol. Figure 1 As shown, PS-b-PAA microspheres were obtained.
[0038] Example 2
[0039] UiO-66-NH has both micropores and mesopores 2 Preparation of microspheres
[0040] 2 ml of 2-aminoterephthalic acid (10 mg / ml) ethanol solution was added to 4 ml of PS-b-PAA microsphere ethanol solution and stirred for 60 minutes. Then, 2 ml of zirconium tetrachloride (ZrCl 4 , 20 mg / ml) ethanol solution, 2 ml (3 M) formic acid aqueous solution. The resulting mixture was placed in an oil bath (70 °C) for 12 h. 2The reaction mixture was cooled to room temperature, the precipitate was collected by centrifugation, and the precipitate was washed several times with ethanol and ultrapure water. Figure 2 The reaction was carried out at 70 °C for 12 h, and the solvent was ethanol. PS-b-PAA@UiO-66-NH 2 Microspheres.
[0041] The prepared composite material PS-b-PAA@UiO-66-NH 2 The microspheres were immersed in N,N'-dimethylformamide (DMF) to dissolve the block copolymer PS-b-PAA part, and the resulting product was collected by centrifugation, washed with DMF and methanol several times, and finally dried at 60 °C under vacuum for 12 h. Figure 3 The results show that the UiO-66-NH 2 Microspheres.
[0042] Example 3
[0043] Preparation of ZIF-67 microspheres with both micropores and mesopores
[0044] 2 ml of 2-methylimidazole (HMeIM, 40 mg / ml) methanol solution was added to 4 ml of PS-b-PAA microsphere methanol solution and stirred for 60 min. Then, 2 ml of Co(NO 3 ) 2 6H 2 O (35 mg / ml) methanol solution. The resulting mixture was then stirred at room temperature for 24 h. The PS-b-PAA@ZIF-67 reaction mixture was cooled to room temperature, the precipitate was collected by centrifugation, and the precipitate was washed several times with methanol. Figure 4 The organic ligand: metal molar ratio was 4=1, and the reaction was carried out for 24 hours to obtain PS-b-PAA@ZIF-67 microspheres as shown.
[0045] The prepared composite PS-b-PAA@ZIF-67 microspheres were immersed in N, N'-dimethylformamide (DMF) to dissolve the block copolymer PS-b-PAA part, and the resulting product was collected by centrifugation and then washed with DMF and methanol several times. Then it was dried under vacuum at 60 °C for 12 h. Figure 5 As shown, ZIF-67 microspheres with both micropores and mesopores were produced.
[0046] Example 4
[0047] Take 100 mg of UiO-66-NH synthesized in Example 2 2 The microspheres were subjected to Brunauer-Emmet-Teller (BET) analysis by Figure 6 It can be observed that the specific surface area is 882.86m 2 / g, N was determined by DFT method 2 The adsorption isotherm pore size distribution has an average pore size of 1.7 nm. Figure 6 It can be observed that UiO-66-NH 2 Microspheres have not only micropores but also mesopores.
[0048] Example 5
[0049] 100 mg of the ZIF-67 microspheres synthesized in Example 3 were taken for brunauer-emmet-teller (BET) analysis. Figure 6 It can be observed that the specific surface area is 999.10m 2 / g, N was determined by DFT method 2 The adsorption isotherm pore size distribution has an average pore size of 1.15 nm. Figure 7 It can be observed that ZIF-67 microspheres have not only micropores but also mesopores.
[0050] Example 6
[0051] Take 5 mg of UiO-66-NH synthesized in Example 2 2 The microspheres were immersed in different organic solvents (DCM, DMF, THF, DMSO) for 12 h, washed by ethanol centrifugation, and placed in a 60 °C vacuum drying oven overnight. Figure 8 It can be observed that at 7.42 0 ,8.59 0 , 25.78 0 , 30.78 0 The characteristic peaks did not shift, indicating that UiO-66-NH 2 The structure of the microspheres did not change, proving that the microspheres had good chemical stability.
[0052] Example 7
[0053] 5 mg of the ZIF-67 microspheres synthesized in Example 3 were immersed in different organic solvents (DCM, DMF, THF, DMSO) and allowed to stand for 12 h. After centrifugal washing with ethanol, they were placed in a vacuum drying oven at 60 °C overnight. The microspheres were characterized by powder X-ray diffractometer (PXRD). Fig. 9 It can be observed that in 7.1 0 The characteristic peaks did not shift, indicating that the structure of ZIF-67 microspheres did not change when immersed in different organic solvents, proving that the microspheres have good chemical stability.
[0054] Example 8
[0055] Methylene blue (MB) aqueous solution was used to simulate the pollutant and UiO-66-NH2 The microspheres were used as adsorbents. 5 mg of the adsorbents were immersed in an aqueous solution of organic dyes with an initial concentration of 20 and 40 mg / L. The adsorption experiment was carried out at a given time. After the adsorption was completed, the adsorbent was removed by filtering with a 0.22 μm microporous PES membrane and the filtrate was collected. The maximum adsorption wavelength of MB was observed at 664 nm using an ultraviolet spectrophotometer. The UiO-66-NH 2 The adsorption capacity of the microspheres for methylene blue was studied, and the adsorption capacity at different concentrations and different times was studied. Fig.10 It can be observed that the methylene blue (MB) aqueous solution can be rapidly adsorbed within 30 min. The initial concentration of the methylene blue aqueous solution was 20-80 mg / L, and the simulated adsorption was carried out at 20℃, 30℃, 40℃, and 50℃. The higher the temperature, the greater the adsorption capacity.
[0056] At room temperature, UiO-66-NH 2 The adsorption capacity of the microspheres at 20 mg / L methylene blue for 30 min was 108.16 mg / g, with a removal rate of 93.85%. The adsorption capacity at 40 mg / L methylene blue for 30 min was 182.38 mg / g, with a removal rate of 85.83%. Fig.10 It can be observed that at the same concentration and adsorption time, the adsorption rate of UiO-66-NH 2 Compared with nanoparticle adsorption, the adsorption capacity is 1.31~1.36 times larger. The adsorption rate is greater and the removal rate is higher.
[0057]
[0058] where q e is the adsorption capacity (mg / g) at equilibrium time t (min), C 0 is the initial concentration of methylene blue (mg / L), C e is the concentration of methylene blue at adsorption equilibrium (mg / L), V is the volume of the adsorption solution (mL), m is the mass of the adsorbent (g), and E is the dye removal efficiency (%).
[0059] Example 9
[0060] Using Cr (VI) solution as a simulated pollutant, ZIF-67 microspheres were used for the adsorption of hexavalent chromium ions: 5 mg of the adsorbent was immersed in a potassium dichromate solution with an initial concentration of 5 and 10 mg / L, and the adsorption experiment was carried out at a given time. After the adsorption experiment was completed, the adsorbent was removed by filtering with a 0.22 μm microporous PES membrane and the filtrate was collected. Using diphenylcarbazide as a color developer and a UV-visible spectrophotometer, it can be observed that the maximum adsorption wavelength of Cr (VI) is at 540 nm. The adsorption capacity of ZIF-67 microspheres for methylene blue was calculated according to Formula 1, and the adsorption capacity at different concentrations and different times was studied. Fig.11 It can be observed that Cr (VI) solution can be rapidly adsorbed within 90 min. The initial concentration of Cr (VI) aqueous solution was 5-40 mg / L, and simulated adsorption was carried out at 20℃, 30℃, 40℃, and 50℃, respectively. The higher the temperature, the greater the adsorption capacity.
[0061] At room temperature, the adsorption capacity of ZIF-67 microspheres in 5 mg / L Cr (VI) solution for 90 min was 19.9 mg / g, and the removal rate was 91.18%. The adsorption capacity of ZIF-67 microspheres in 10 mg / L Cr (VI) solution for 90 min was 26.25 mg / g, and the removal rate was 84.51%. Fig.11 It can be observed that at the same concentration and adsorption time, the adsorption amount is 1.47~1.49 times larger, the adsorption rate is greater, and the removal rate is higher compared with the adsorption of ZIF-67 nanoparticles alone.
[0062] Comparative Example 1
[0063] PS-b-PAA@UiO-66-NH 2 The preparation of microspheres is basically the same as in Example 2, and other conditions remain unchanged. The difference is that only the solvent, reaction temperature, and reaction time are changed to conduct the following screening experiments:
[0064] In Example 3, ethanol was used as the reaction solvent and the reaction was carried out in an oil bath at 70° C. for 12 h.
[0065] (1) Disperse 2-aminoterephthalic acid (10 mg / ml) in 2 ml of different solvents (ultrapure water, DMF) as solution a, and add zirconium tetrachloride (ZrCl 4 , 20 mg / ml) was dispersed into 2 ml (ultrapure water, DMF) and recorded as solution b.
[0066] (2) Solution a was mixed with 4 ml of PS-b-PAA microsphere alcohol solution, 3 M formic acid aqueous solution was added and stirred for 60 min, then solution b was added and the resulting mixture was placed at different temperatures (30 °C, 100 °C).
[0067] (3) The reaction time is 5h.
[0068] PS-b-PAA@UiO-66-NH 2 The reaction mixture was cooled to room temperature, the precipitate was collected by centrifugation, and the precipitate was washed several times with ethanol and ultrapure water.
[0069] pass Figure 2 By observing the SEM images under different preparation conditions, it can be found that when ultrapure water is used as the solvent, the surface of the PS-b-PAA microspheres appears to be agglomerated spherical. When DMF is used as the solvent, DMF will dissolve the PS-b-PAA microspheres and the microspheres will rupture. When ethanol is used as the solvent, UIO-66-NH 2 Nanoparticles grow well on the surface of microspheres.
[0070] When the reaction temperature was 30 °C and the reaction time was 5 h, it was observed that the MOF particles did not grow completely. When the reaction temperature was 100 °C, the temperature was too high to destroy the polymer soft template morphology and the microspheres broke. Therefore, by screening the conditions, UIO-66-NH 2 The best conditions for the microspheres were to use ethanol as the reaction solvent and react in an oil bath at 70 °C for 12 h.
[0071] Comparative Example 2
[0072] The preparation of PS-b-PAA@ZIF-67 microspheres was basically the same as in Example 3, with other conditions unchanged, except that only the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate, the concentration of 2-methylimidazole to cobalt nitrate hexahydrate methanol solution, and the reaction time were changed to conduct the following screening experiments:
[0073] In Example 3, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is 4:1, the concentrations of 2-methylimidazole and cobalt nitrate hexahydrate methanol solution are 40 mg / L and 35 mg / L, respectively, and the reaction is carried out for 24 hours.
[0074] (1) 2-Methylimidazole (HMeIM) alcohol solution was added to the PS-b-PAA microsphere alcohol solution and stirred for 60 minutes. Then, cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O) alcohol solution. The molar ratios of 2-methylimidazole and cobalt nitrate hexahydrate are 1:1 and 2:1 respectively.
[0075] (2) Add 2 ml (20 mg / L) 2-methylimidazole (HMeIM) methanol solution to 4 ml PS-b-PAA microsphere alcohol solution and stir for 60 min. Then add 2 ml (17.5 mg / L) cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2O) alcohol solution.
[0076] (3) The resulting mixture was stirred at room temperature for 5 h and 12 h respectively.
[0077] The PS-b-PAA@ZIF-67 reaction mixture was cooled to room temperature, and the precipitate was collected by centrifugation and washed with methanol several times.
[0078] pass Figure 4 By observing the SEM images of PS-b-PAA@ZIF-67 microspheres under different reaction conditions, it can be found that with the increase of the molar ratio, the particle size of ZIF-67 decreases accordingly. When the molar ratio of organic ligand to metal is 4:1, ZIF-67 nanoparticles grow well on PS-b-PAA microspheres. When the concentrations of 2-methylimidazole and cobalt nitrate hexahydrate ethanol solution are 20 mg / L and 17.5 mg / L, respectively, fewer ZIF-67 nanoparticles are formed on the surface of PS-b-PAA microspheres. When the reaction time is 5h and 12h, the ZIF-67 precursor solution does not react fully with the PS-b-PAA microspheres. Therefore, through screening conditions, the optimal conditions for synthesizing ZIF-67 microspheres are a molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate of 4:1, and the concentrations of 2-methylimidazole and cobalt nitrate hexahydrate ethanol solution are 40 mg / L and 35 mg / L, respectively, and the reaction is carried out at room temperature for 24h.
[0079] Comparative Example 3
[0080] UiO-66-NH 2 Preparation of nanoparticles
[0081] 40 mg ZrCl 4 , 20 mg of diaminoterephthalic acid, and 4 mL of ethanol were added to 3 mL of 30% formic acid in sequence, placed in an ultrasonic system for 10 min, and completely dissolved, transferred to an oil bath at 70 °C and stirred for 12 h, and washed with anhydrous ethanol and deionized water for 3 to 5 times. Finally, dried at 60 °C in vacuum for 12 h to obtain UiO-66-NH 2 Nanoparticles.
[0082] Methylene blue (MB) aqueous solution was used to simulate the pollutant and UiO-66-NH 2 Nanoparticles were used as adsorbents. 5 mg of the adsorbent was immersed in an aqueous solution of an organic dye with an initial concentration of 20 and 40 mg / L. The adsorption experiment was carried out at a given time. After the adsorption was completed, the adsorbent was removed by filtering with a 0.22 μm microporous PES membrane and the filtrate was collected. The maximum adsorption wavelength of MB was observed at 664 nm using an ultraviolet spectrophotometer. The UiO-66-NH 2 The adsorption capacity of nanoparticles for methylene blue is shown in Table 1. At room temperature, the adsorption capacity of UiO-66-NH2 The adsorption capacity of nanoparticles was 79.529 mg / g, and the adsorption capacity at different concentrations and different times was studied. The dye removal rate was calculated using Formula 2. The removal rate of methylene blue at 20 mg / L was 87.41%, and the removal rate of UiO-66-NH 2 The adsorption capacity of nanoparticles is 139.21 mg / g, and the removal rate is 77.36%.
[0083] Comparative Example 4
[0084] Preparation of ZIF-67 nanoparticles
[0085] Dissolve 35 mg of Co(NO 3 ) 2 6H 2 O and 40 mg 2-methylimidazole. The latter transparent solution was added to the former pink solution, and the components were mixed and stirred for 24 h. The purple solid was collected by centrifugation, washed with methanol three times, and dried at 60 °C for 12 h.
[0086] Taking Cr (VI) as the simulated pollutant, ZIF-67 nanoparticles were used for the adsorption of hexavalent chromium ions: 5 mg of the adsorbent was immersed in a potassium dichromate solution with an initial concentration of 5 and 10 mg / L, and the adsorption experiment was carried out at a given time. After the adsorption was completed, the adsorbent was removed by filtration with a 0.22 μm microporous PES membrane and the filtrate was collected. After the adsorption experiment was completed, the adsorbent was removed by filtration with a 0.22 μm microporous PES membrane and the filtrate was collected. Using diphenylcarbazide as a color developer and a UV-visible spectrophotometer, it can be observed that the maximum adsorption wavelength of Cr (VI) is 540nm. The adsorption capacity of ZIF-67 nanoparticles for Cr (VI) solution is calculated according to formula 1. The adsorption capacity of ZIF-67 nanoparticles is 13.537 mg / g when the Cr (VI) solution is 5 mg / L. The adsorption capacity at different concentrations and times is studied. At room temperature, the adsorption capacity of ZIF-67 microspheres at 5 mg / L Cr (VI) solution for 30 min is 13.47 mg / g. According to formula 2, the heavy metal ion removal rate of 5 mg / LCr (VI) solution is 82.18%, the adsorption capacity at 10 mg / L Cr (VI) solution for 30 min is 17.62 mg / g, and the heavy metal ion removal rate of 10 mg / LCr (VI) solution is 76.25%.
Claims
1. Application of a metal organic framework microsphere material with both micropores and mesopores in organic dye and heavy metal wastewater, characterized by: MOF is grown on the surface and in the pores of the amphiphilic block polymer mesoporous microspheres by a soft template method, and then the polymer microspheres are dissolved by a polymer good solvent to form metal organic framework MOF microspheres with both micropores and mesopores, which are UiO-66-NH2 microspheres or ZIF-67 microspheres; UiO-66-NH2 microspheres are used to adsorb methylene blue solution, and ZIF-67 microspheres are used to adsorb Cr (VI) solution; The preparation method of the metal organic framework microspheres is as follows: (1) dissolving a block copolymer of polystyrene-block-polyacrylic acid in a mixed solvent of toluene / methanol, stirring for a certain period of time under magnetic stirring, and then adding a large amount of methanol to fix the obtained mesoporous spheres, collecting the obtained mesoporous spheres by centrifugation, and dispersing the mesoporous spheres in an alcohol solution to obtain a solution 1; (2) Add 2-aminoterephthalic acid or 2-methylimidazole solution into the above solution 1, and stir the two substances to form solution 2; (3) Add zirconium tetrachloride or cobalt nitrate hexahydrate alcohol solution to solution 2, stir continuously for 12 h to 24 h in an oil bath or at room temperature, and then cool to room temperature, which is recorded as solution 3; (4) Solution 3 is centrifuged to obtain a product, which is washed with DMF to remove the polymer soft template and then dried in a vacuum oven for 12-24 h. The obtained substance is a metal organic framework microsphere particle having both micropores and mesopores.
2. The use of the metal organic framework microsphere material with both micropores and mesopores in organic dye and heavy metal wastewater according to claim 1, characterized in that: 2 ml of 10 mg / ml ethanol solution of 2-aminoterephthalic acid was added to 4 ml of alcohol solution of PS-b-PAA microspheres and stirred for 60 minutes, followed by addition of 2 ml of 20 mg / ml ethanol solution of zirconium tetrachloride and 2 ml of 3M aqueous formic acid; the resulting mixture was placed in an oil bath at 70°C for 12 hours; the PS-b-PAA@UiO-66-NH2 reaction mixture was then cooled to room temperature, the precipitate was collected by centrifugation, and the precipitate was washed several times with ethanol and ultrapure water to obtain PS-b-PAA@UiO-66-NH2 microspheres; the prepared composite material PS-b-PAA@UiO-66-NH2 microspheres were immersed in N,N'-dimethylformamide to dissolve the block copolymer PS-b-PAA part, the resulting product was collected by centrifugation, and washed several times with DMF and methanol; finally, it was dried at 60°C under vacuum conditions for 12 hours to produce UiO-66-NH2 microspheres with both micropores and mesopores; 2 ml of 2-methylimidazole 40 mg / ml methanol solution was added to 4 ml of PS-b-PAA microsphere methanol solution and stirred for 60 minutes, followed by the addition of 2 ml of Co(NO3)2·6H2O 35 mg / ml methanol solution; the resulting mixture was then stirred at room temperature for 24 hours; the PS-b-PAA@ZIF-67 reaction mixture was cooled to room temperature, the precipitate was collected by centrifugation, and the precipitate was washed several times with methanol to obtain PS-b-PAA@ZIF-67 microspheres; the prepared composite material PS-b-PAA@ZIF-67 microspheres were immersed in N, N'-dimethylformamide to dissolve the block copolymer PS-b-PAA part, the resulting product was collected by centrifugation, and then washed several times with DMF and methanol; and then dried at 60 ° C under vacuum conditions for 12 hours to produce ZIF-67 microspheres with both micropores and mesopores.
3. The use of the metal organic framework microsphere material with both micropores and mesopores in organic dye and heavy metal wastewater according to claim 2, characterized in that: When 5 mg of amino metal organic framework UiO-66-NH2 microspheres were added to 20 mol / L methylene blue solution and stirred at room temperature for 30 min, the maximum adsorption rate could reach 93.85%; when 5 mg of metal organic framework ZIF-67 microspheres were added to 5 mol / L Cr (VI) solution and stirred at room temperature for 90 min, the maximum adsorption rate could reach 90.18%.
4. The use of the metal organic framework microsphere material with both micropores and mesopores in organic dyes and heavy metal wastewater according to claim 1, characterized in that: Mesoporous polymer microspheres were used as soft templates and synthesized through a simple hydrothermal method. UiO-66-NH2 and ZIF-67 micron-sized microspheres with both microporous and mesoporous pore sizes were formed by the mutual growth of metal-organic framework nanocrystals. The synthesis steps were simplified and green solvents such as ethanol and methanol were used.
5. The use of metal organic framework microsphere materials with both micropores and mesopores in organic dyes and heavy metal wastewater according to claim 1, characterized in that: The concentrations of 2-aminoterephthalic acid, dimethylimidazole, zirconium tetrachloride and chromium nitrate hexahydrate alcohol solution are all 10-40 mol / L.
6. The use of the amino metal organic framework UiO-66-NH2 microspheres according to claim 1 in treating the organic dye methylene blue, characterized in that: The concentration of methylene blue water adsorbed at room temperature is 20-40 mol / L, and the concentration of Cr (VI) solution adsorbed at room temperature is 5-10 mol / L.
7. The use of the amino metal organic framework UiO-66-NH2 microspheres according to claim 1 in treating a methylene blue aqueous solution, characterized in that: The adsorption process of the amino metal organic framework UiO-66-NH2 microspheres after adsorbing methylene blue solution is irreversible at 20-50°C. A control group is set up. Compared with the adsorption of UiO-66-NH2 nanoparticles alone, the adsorption capacity of MOF microspheres with both micropores and mesopores is higher, and the material can exist stably after being immersed in other organic solvents for a period of time, and has good chemical stability.
8. The use of the metal organic framework ZIF-67 microspheres in treating Cr (VI) solution according to claim 1, characterized in that: The adsorption process of the metal organic framework ZIF-67 microspheres after adsorbing Cr (VI) solution is irreversible at 20-50°C, and the adsorption capacity is higher than that of ZIF-67 nanoparticles alone. After being immersed in other organic solvents for a period of time, the material can exist stably and has good chemical stability.
Citation Information
Patent Citations
Olefin-alkane separating adsorbent and preparation method and application thereof
CN103007885A
Controllable preparation method of self-supporting two-dimensional mesoporous nano material
CN113353917A
Synthesis method and application of MOFs (Metal-Organic Frameworks) with hierarchical pore structure
CN117417547A
Controllable preparation method and application of mesoporous and macroporous adjustable graded pore pi-complexed MOFs (Metal-Organic Frameworks) adsorption material
CN118185040A
Block coordination copolymers
WO2010099143A2
Cited By
Fluorine-containing wastewater treatment method and treatment agent thereof
CN120736657A
UiO-66 / macroporous resin composite material, preparation method and application
CN122479736A
UiO-66 / macroporous resin composite material, preparation method and application
CN122479736B